2000
DOI: 10.1080/000368400322516
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of outbound tourism demand in the UK

Abstract: A general to specific methodology is used to construct UK demand for outbound tourism models to twelve destinations. A tourism destination preference index is introduced to take into account social, cultural and psychological influences on tourists' decisions concerning their overseas holiday destinations. The tests support the existence of a cointegration relationship for each of 11 UK overseas holiday destinations. The corresponding error correction models are estimated. The empirical results show that the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
87
0
7

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(96 citation statements)
references
References 29 publications
2
87
0
7
Order By: Relevance
“…In addition to own price, Kim and Song (1998), Song et al (2000), Song and Witt (2003), and Song and Witt (2006) showed that substitute prices in competitive destinations are important determinants. There are two kinds of substitute prices: one allows for the substitution between the destination and a competitive destination, and the other calculates the cost of tourism in the destination under consideration relative to a weighted average cost of living in various competing destinations, and this index is also adjusted by relevant exchange rates.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to own price, Kim and Song (1998), Song et al (2000), Song and Witt (2003), and Song and Witt (2006) showed that substitute prices in competitive destinations are important determinants. There are two kinds of substitute prices: one allows for the substitution between the destination and a competitive destination, and the other calculates the cost of tourism in the destination under consideration relative to a weighted average cost of living in various competing destinations, and this index is also adjusted by relevant exchange rates.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, alternative income measures have to be used as a proxy for tourists' discretionary income. Among these alternatives, such as GDP, gross national product (GNP), PDI, and gross national income (GNI), real PDI is the best proxy to include in the demand models relating to holidays or travel to visit friends and relatives (Kulendran and Witt 2001;Song et al 2000;Song and Witt 2006). Therefore, the monthly data of real PDI is chosen as one of the economic factors in this paper.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The developed countries have been an important source of the international market for a long time and the initial outbound tourism research focused on their demand patterns. For example, Song et al (2000) studied the UK's outbound tourism demand, which was applied in 12 different destinations and their findings show that the income and price elasticity of demand is quite high for travels to overseas countries. Hamal (1998) studied the Australian outbound holiday travel demand and the author concluded that the demand was affected highly by domestic travel and accommodation prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A typical social variable is the social status of tourists (Moeran, 1983;Mok & Defranco, 2000;Song, et al, 2000). In order to better understand the relationship between social status and tourism demand, we borrowed two concepts from economics and sociology, namely, "conspicuous consumption" and "positional good".…”
Section: Social Status and Tourism Demandmentioning
confidence: 99%